Effectiveness of Technology-Enhanced Inquiry-Based Learning: A Meta-Analysis with Implications for Islamic Education - Maria dewi, Ai Deudeu; Thohir , Ajid; Nursobah, Asep; Suntiah, Ratu (Jurnal Pendidikan Islam, 2025)
Purpose – Technology-Enhanced Inquiry-Based Learning (TE-IBL) is widely regarded as effective for fostering 21st-century competencies. However, empirical findings remain inconsistent across studies, and synthesis that systematically accounts for key moderators is still limited, particularly within Islamic Education contexts that require the integration of spiritual values and digital ethics. This study aims to estimate the overall effect of TE-IBL on learning outcomes and to examine how contextual and instructional moderators shape its effectiveness. Design/methods/approach – This study followed the PRISMA 2020 guidelines for systematic review and meta-analysis. From 16,742 initial records, 47 studies met the inclusion criteria. A random-effects model using Restricted Maximum Likelihood (REML) estimation and Hedges’ g was employed to calculate effect sizes. Heterogeneity was assessed using Q, τ², and I² statistics. Moderator analyses included educational level, subject domain, inquiry type, technology type, and intervention duration. Publication bias was examined using Egger’s regression test, complemented by leave-one-out sensitivity analysis. Findings – The pooled effect size indicated a significant and large effect of TE-IBL on learning outcomes (g = 0.92; SE = 0.108; 95% CI = 0.61–1.03; p < 0.001), with substantial heterogeneity (I² = 67.99%). Problem-Based Learning yielded the highest effect (g = 1.20), followed by guided inquiry (g = 0.79) and project-based learning (g = 0.72). Social and humanities subjects showed stronger effects than STEM (g = 1.06 vs. 0.74). Non-AI technologies outperformed AI-based technologies (g = 1.05 vs. 0.52). Longer interventions (>2 months) produced the largest effects (g = 1.37). Across educational levels, early childhood education demonstrated the highest effect size (g = 2.49), while lower secondary education showed the lowest (g = 0.47). Egger’s test indicated potential funnel plot asymmetry (z = 2.30; p = 0.021). Research implications – High heterogeneity and indications of publication bias constrain generalizability and call for cautious interpretation. Design-related factors such as inquiry scaffolding, intervention duration, and technology selection substantially influence outcomes. Practically, TE-IBL implementation should emphasize teacher professional development, value-sensitive technological design, and ethical integration aligned with Islamic educational principles. Future research should expand geographic coverage, adopt preregistered designs, and more rigorously integrate AI within a framework of ethically grounded and sustainable education.